Cognitive approaches to specialist languages - Grygiel, Marcin (Cambridge Scholars Publishing, 2017)
Specialist languages, such as the languages of law, business, aviation, football, and politics, can be perceived as highly conventionalized, semi-natural and not fully autonomous communication codes limited to specific, and predominantly formal, situations. A large number of them can be best characterized by subject matter and semantic content, but the most important distinctive element in their make-up is the frame of context in which they are embedded. This volume discusses various ways of approaching the problems associated with the very broad phenomenon of specialist languages by means of.